Zwischen Babel und Jerusalem: Aspekte von Sprache und Ubersetzung - Ziegert, Carsten (European journal of theology, 2019)
In eleven interdisciplinary contributions (four of them original ones) this volume offers a critique of dynamic-equivalent Bible translations. Theologians, philosophers and literary translators emphasise the significance of the Luther Bible. The concern for furthering knowledge and use of the Bible is obvious, but not all the viewpoints which are brought forward are convincing. A non-European missiological perspective is lacking. (English)